2022
DOI: 10.1186/s12964-022-00915-2
|View full text |Cite
|
Sign up to set email alerts
|

Slc2a6 regulates myoblast differentiation by targeting LDHB

Abstract: Background Type 2 diabetes mellitus is a global health problem. It often leads to a decline in the differentiation capacity of myoblasts and progressive loss of muscle mass, which in turn results in deterioration of skeletal muscle function. However, effective therapies against skeletal muscle diseases are unavailable. Methods Skeletal muscle mass and differentiation ability were determined in db/+ and db/db mice. Transcriptomics and metabolomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is also possible that each transporter could be expressed in one or more distinct cell types found within overload-stimulated muscle tissue. For example, while GLUT1 has been detected in myocytes and endothelial cells [ 34 , 35 , 36 , 37 , 38 ]; GLUT3 has been detected in myocytes and neurons [ 52 , 53 ]; GLUT6 in myocytes, endothelial, and immune cells [ 54 , 55 , 56 ]; and GLUT10 in myocytes and vascular smooth muscle cells [ 53 , 57 ]. Prior work in rat muscle has demonstrated that 1 week of mechanical overload is sufficient to increase the capillary density to muscle fiber ratio [ 58 ]; providing a possible explanation for the induction of endothelial cell-derived GLUTs.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that each transporter could be expressed in one or more distinct cell types found within overload-stimulated muscle tissue. For example, while GLUT1 has been detected in myocytes and endothelial cells [ 34 , 35 , 36 , 37 , 38 ]; GLUT3 has been detected in myocytes and neurons [ 52 , 53 ]; GLUT6 in myocytes, endothelial, and immune cells [ 54 , 55 , 56 ]; and GLUT10 in myocytes and vascular smooth muscle cells [ 53 , 57 ]. Prior work in rat muscle has demonstrated that 1 week of mechanical overload is sufficient to increase the capillary density to muscle fiber ratio [ 58 ]; providing a possible explanation for the induction of endothelial cell-derived GLUTs.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Our previous study also confirmed the detrimental effect of lactate accumulation on myogenic differentiation and the down‐regulation of PDHB expression during this process. 28 How PDHB regulates glycolysis and lactate production in the skeletal muscle needs further study.…”
Section: Discussionmentioning
confidence: 99%